2021
DOI: 10.1038/s41598-021-98002-y
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of genotype × environment interaction for identification of stable genotypes for tillering phase drought stress tolerance in sugarcane

Abstract: Sugarcane is a trans-seasonal long-duration crop and tillering phase (60–150 days) is the most sensitive phase for moisture stress, causing significant reduction in biomass accumulation. The study focussed to assess the Genotype × Environment Interaction (GEI) for tillering phase moisture stress and to identify the stable genotypes in sugarcane. The study dealt with 14 drought tolerant genotypes and two standards (Co 86032 and CoM 0265) which were evaluated in two plant and one ratoon trials at four locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Therefore, increasing stem diameter would increase crossed clones' stem weight. Mahadevaiah et al (2021) show a positive correlation between stem weight, length, and diameter.MLG 19/P6/13 and MLG 19/P6/16 had the highest number of stems (94255-97200 stems/ha). MLG 19/P6/12 had the least number of stems (50625 stems/ha).…”
Section: Finding and Discussion Plant Growthmentioning
confidence: 85%
“…Therefore, increasing stem diameter would increase crossed clones' stem weight. Mahadevaiah et al (2021) show a positive correlation between stem weight, length, and diameter.MLG 19/P6/13 and MLG 19/P6/16 had the highest number of stems (94255-97200 stems/ha). MLG 19/P6/12 had the least number of stems (50625 stems/ha).…”
Section: Finding and Discussion Plant Growthmentioning
confidence: 85%
“…Indeed, this parameter provides simultaneous selection for productivity and phenotypic stability in the context of a mixed model. Results of the study performed by Mahadevaiah et al [ 68 ] in the delineation of genotype × environment interaction for identification of stable genotypes of sugarcane revealed that screening of drought-tolerant and stable genotypes using the GSI parameter has a considerable association with the multi-environment BLUP results, so this parameter could be used as an ideal indicator in the similar experiments. Verma and Singh [ 67 ] identified the high-yielding and stable genotypes of wheat using HMRPGV parameter.…”
Section: Deciphering Ge Interaction Using Different Statistical Methodsmentioning
confidence: 99%
“…(3)The sugarcane variety is required to have the desired growth characteristics, such as quick and even germination, emergence, and tillering, a high rate of stalk formation from tillers, uniform growth rate of the plants, and minimal sprouting in autumn and winter. After planting, robust seedlings with uniform growth can grow as quickly as possible, forming a seedling population with vigorous and even growth, which facilitates inter-row cultivation and helps to improve work efficiency and minimize damage to sugarcane seedlings during mechanical operation ( Pierre et al., 2019 ; Mahadevaiah et al., 2021 ; Meena et al., 2022 ; Wang T. et al., 2023 ).…”
Section: Requirements For Sugarcane Varieties In Mechanized Productionmentioning
confidence: 99%